The right to the truth in the genocide of the Patriotic Union (2021)
This article seeks to understand, explain and address the concept of genocide as an internationally repudiated criminal type, and the antecedents of the conceptualization of the type, since it is no less true that the concept of genocide was legally coined until the second half of the last century as a product of the great wars and micro wars that some European states lived after the Second World War. In this way, understanding the concept will allow the laying of sufficient bases to address its application in a more specific stage such as that of the Colombian State.   Once the general concept has been approached, the normative application that the Colombian State gave to the type of genocide will be analyzed, given the newest addition of the type for political reasons, which changes the original meaning, since it is understood within an unusual, atypical and strange context for the international community and allows in-depth investigation of the component (of all transitional justice) of truth within the recognition of justice, since this is vital to provide reparation and guarantee justice, not only to the victims, but also to the entire Colombian and international society as an element of integrity between the judicial apparatus, the victims, the national government and society, and for this reason forging a wide degree of general judicial security within the Colombian State.